Translating COVID-19 Evidence to Maximize Physical Therapists' Impact and Public Health Response. Issue 9 (31st July 2020) - Dean, Elizabeth; Jones, Alice; Yu, Homer Peng-Ming; Gosselink, Rik; Skinner, Margot
Abstract: Coronavirus disease 2019 (COVID-19) has sounded alarm bells throughout global health systems. As of late May, 2020, over 100, 000 COVID-19–related deaths were reported in the United States, which is the highest number of any country. This article describes COVID-19 as the next historical turning point in the physical therapy profession's growth and development. The profession has had over a 100-year tradition of responding to epidemics, including poliomyelitis; 2 world wars and geographical regions experiencing conflicts and natural disasters; and, the epidemic of noncommunicable diseases (NCDs). The evidence-based role of noninvasive interventions (nonpharmacological/nonsurgical) that hallmark physical therapist practice has emerged as being highly relevant today in addressing COVID-19 in 2 primary ways. First, despite some unique features, COVID-19 presents as acute respiratory distress syndrome in its severe acute stage. Acute respiratory distress syndrome is very familiar to physical therapists in intensive care units. Body positioning and mobilization, prescribed based on comprehensive assessments/examinations, counter the negative sequelae of recumbency and bedrest; augment gas exchange and reduce airway closure, deconditioning, and critical illness complications; and maximize long-term functional outcomes. Physical therapists have an indisputable role across the contiuum of COVID-19 care. Second, over 90% of individuals who die from COVID-19 have comorbidities, most notably cardiovascular disease, hypertension, chronic lung disease, type 2 diabetes mellitus, and obesity. Physical therapists need to redouble their efforts to address NCDs by assessing patients for risk factors and manifestations and institute evidence-based health education (smoking cessation, whole-food plant-based nutrition, weight control, physical activity/exercise), and/or support patients' efforts when these are managed by other professionals. Effective health education is a core competency for addressing risk of death by COVID-19 as well as NCDs. COVID-19 is a wake-up call to the profession, an opportunity to assert its role throughout the COVID-19 care continuum, and augment public health initiatives by reducing the impact of the current pandemic.